STRATEGI PENGEMBANGAN EKOWISATA DI DESA RANTAU LANGAT TAMAN NASIONAL BUKIT TIGA PULUH KABUPATEN INDRAGIRI HULU - Novhira Rahmatika MR; Abdul Sadad (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Rantau Langsat village is one of the villages with rich ecotourism in Batang Gangsal District, Indragiri Hulu Regency which has abundant natural potential that can be made into a leading destination if managed properly. So there is a need for a special strategy in the development of Ecotourism in Rantau Langsat Village, Bukit Tiga Puluh National Park, where this strategy will be used by human resources who handle it in the Bukit Tiga Puluh National Park Agency. This study uses a descriptive qualitative research method. Based on the SWOT analysis, the strategic recommendation given is an Aggressive Strategy where this situation is very profitable, because the strengths you have can be utilized for existing opportunities. The results of this study indicate that the development of ecotourism in Rantau langsat Village, Bukit Tiga Puluh National Park, Indragiri Hulu Regency has many obstacles, so the resulting strategy can optimize the promotion of the Batang Gangsal Festival through social media and by utilizing technological advances and information that is growing, the existence of work from several stakeholders so as to make the tourism climate more developed and create innovations in the world of tourism and also the Minister of Home Affairs regarding tourist guidelines so that it helps the community to be able to take advantage of these opportunities.